Between Mass and Individual. Vilnius Special Squad 1941–1945 - Šikšnianas , Mantas (Genocidas ir rezistencija, 2016)
The subject of the article is Vilnius special squad (Sonderkommando), one of the main formations, which carried out mass extermination of people in Vilnius and Vilnius region during the Nazi occupation. The process of its formation is revealed together with the motivation of its members (it is likely that those who joined the squad did it predominantly because of material gain). One of the specific features of the formation of the squad was connections of its members (new members were often recruited by the existing members of the squad).One of the most important parts of the research was to reconstruct the day-to-day activities of the squad. Consequently, the likely model of the daily routine of the squad was reconstructed from a string of episodes: standing on guard at the “base”, the first night shot, standing on guard at night in Paneriai, and other moments are described. The article also reveals the people’s attitudes towards the members of the special squad.Finally, the article discusses the withdrawal of the special squad from Lithuania and the fates of its members after the war. The squad left Lithuania in 1944 and in 1945 operated in Poland as a formation. With the approach of the Soviet Army, its members fled. After the war, around 20 members of the special squad were either sentenced to imprisonment or to death, other members fled mainly to Great Britain, the United States of America and Australia.
Keywords: Lithuania; German occupation; Holocaust; collaborators